Hidrogenação do ácido levulínico a gama-valerolactona empregando catalisadores de níquel suportado em nanotubos de carbono - Sosa, Letícia Forrer (2018)
Nickel and nickel phosphide catalysts supported on carbon nanotubes with loading of 10 wt% were synthesized, characterized and evaluated in the hydrogenation reaction of levulinic acid to γ-valerolactone. The catalysts were synthesized in situ by temperature programmed reduction of the precursors prepared by incipient wetness impregnation followed by calcination. In this dissertation, the nature of the nickel salt (nitrate, acetate and nickel hydroxide) used in the preparation and the positioning of the metallic particles (inside or outside the nanotubes) were evaluated. The samples were characterized by X ray diffraction, N2 physisorption at -196 ° C, inductively coupled plasma optical emission spectrometry, thermogravimetric analysis, programmed temperature desorption, Fourier-transform infrared spectroscopy, Raman spectroscopy, transmission electronic microscopy. The catalyts evaluation was carried out in a continuous reactor operated at 30 bar H2 and at a temperature of 180 °C. The Ni2P/CNT catalyst has shown the best catalytic performance with total conversion of levulinic acid and GVL selectivity higher than 99 %. The catalysts prepared with nitrate and nickel hydroxide presented similar catalytic activity and were higher than the catalysts prepared with nickel acetate. Regarding the positioning of nickel, the catalysts containing particles located mainly outside the channels of the nanotubes had higher activity.